Performance of Imaging Modalities in the Diagnosis of Hepatocellular Carcinoma: a Systematic Review and Meta-Analysis - Floriani, I.; D’Onofrio, M.; Rulli, E.; Chen, M.-H.; Li, R.; Musicco, L. (Ultraschall in der Medizin - European Journal of Ultrasound, 2013)
Purpose: The recent guidelines published in 2011 suggest the use of only one imaging method for the final imaging diagnosis of hepatocellular carcinoma. To evaluate the methods in the context of the available literature evidence, this systematic review aimed at assessing the relative performance of different imaging techniques currently used in clinical practice. Materials and Methods: MEDLINE and EMBASE were searched from January 1996 to June 2011, with no language limitation. Eligible trials had to be conducted in patients with suspicion or diagnosis of hepatocellular carcinoma; compare at least two of the following imaging modalities: magnetic resonance imaging, computed tomography, ultrasound; have pathological findings as a reference standard. An analysis also including non-comparative studies was performed as a validation of the main comparison results. Results: Of 5,144 screened papers, 16 studies fulfilled the eligibility criteria for the comparative analysis and 65 were eligible for the non-comparative analysis. The overall sensitivity and specificity derived by the pooled analysis were 0.78 and 0.77 for computed tomography, 0.84 and 0.84 for magnetic resonance imaging and 0.86 and 0.77 for ultrasound, respectively. In the pair-wise comparisons, ultrasound showed a statistically better specificity than magnetic resonance imaging (0.86 vs. 0.78; p = 0.014) and a statistically better sensitivity than computed tomography (0.88 vs. 0.78; p = 0.030). Conclusion: The present systematic review did not show an obvious superiority of one imaging method. Since their accuracy is not completely overlapping, the possibility of reaching better performance by combining methods should be considered in future prospective trials.
Keywords: systematic review; hepatocellular carcinoma; diagnostic tests